Religiusitas dan Ketangguhan Mental pada Atlet Futsal - Syaputra, Derri; Istiningtyas, Listya (Indonesian Journal of Behavioral Studies, 2023)
Abstract Futsal is a sport that requires good teamwork between players to score goals. One of the problems that athletes often face is anxiety. This study aims to determine the influence between religiosity and mental toughness on competition anxiety. The method used is a quantitative method with a regression approach. The respondents were 85 futsal athletes from 12 teams participating in the PFL (Pelsa Futsal League) tournament. The sampling technique in this study used all populations. The data collection technique uses a Likert scale. The data collection instrument consisted of the religiosity scale adopted by Amalia & Rohmatun (2022), the mental toughness scale, and the competition anxiety scale adopted by Ikhram et al. (2020). Data analysis was carried out using an assumption test for normality, linearity, multicollinearity, heteroscedasticity, and hypothesis testing with the help of the Statistical Packages of Social Science 25 for Windows program. The data analysis results obtained through multiple linear regression techniques obtained a significance value of 0.022, indicating an influence between religiosity and mental toughness with competition anxiety. Furthermore, the results of data analysis on the variable religiosity with competition anxiety showed a significance value of 0.280. It can be concluded that there is no influence of religiosity on competition anxiety. The effective contribution of 8.9% to the variables of religiosity and mental toughness on competition anxiety, while other factors influence 91.2%. Keywords athlete, futsal, competitive anxiety, mental toughness, religiosity